Permanent education of nursing professionals in the use of games for the development of activities related to adolescents in the School Health Program (Research, Society and Development, 2020)
Even in the globalized world, in which communications occur in practically all social classes and age groups, the media points out that children and adolescents remain unattended in their health demands. The object of study is Permanent Education, as a political-pedagogical guideline, for Nursing professionals in the use of games, it is expected to contribute to the development of activities related to adolescents in the Health at School Program (PSE). It is a descriptive and exploratory study, of qualitative nature, of the type research-action. Data collection will take place through a semi-structured questionnaire applied by the author, through participant observation using the field diary. Educational actions must take place in differents socials spaces, in addition to the health unit itself, especially in a school near the Family Health Clinic. Participants will be Nurses, Nursing Technicians and students of the last year of the undergraduate Nursing course who work or do an internship in the Family Health Strategy (ESF). The implementation of these social technologies, the result of a continuous education process, expands the interaction between different actors, providing greater trust between the adolescent and the nursing professional of the FHS, who together enhance the search for their full citizenship.